Tick Off the Gender Diversity Box: Examining the Cross-Level Effects of Women’s Representation in Senior Management - Dwivedi, Priyanka; Paolella, Lionel (Academy of Management Journal, 2024)
In male-dominated industries, organizations face considerable pressure to enhance women’s representation in top leadership roles. Firms respond to this pressure by increasing gender diversity in senior positions, but often fail to achieve a critical mass of senior women at the top. This raises a key question: What impact does greater gender diversity at the top have on junior women’s career opportunities? We develop an attention-based perspective on gender diversity and theorize that firms with relatively more women in senior management compared to their industry peers are likely to allocate fewer attentional resources, time, and effort toward internal diversity practices. This inadvertently hurts the recruitment of women at lower levels. We propose that one way to mitigate these adverse cross-level spillover effects is to ensure women’s substantive representation on committees responsible for overseeing and monitoring the firm’s diversity and hiring-related decision-making processes. We test our contentions and find support for our model using a panel dataset on the largest U.S. law firms. We conduct several supplemental analyses to provide insights into our findings.